Platinum nanoparticles photo-deposited on SnO2-C composites: An active and durable electrocatalyst for the oxygen reduction reaction. (1st September 2019) - Hussain, Sajid; Kongi, Nadezda; Erikson, Heiki; Rähn, Mihkel; Merisalu, Maido; Matisen, Leonard; Paiste, Päärn; Aruväli, Jaan; Sammelselg, Väino; Estudillo-Wong, Luis Alberto; Tammeveski, Kaido; Alonso-Vante, Nicolas
Abstract: Platinum nanoparticles (NPs) were photo-deposited on SnO2 -C nanocomposites prepared by sol-gel method. Surface morphology of the prepared materials, examined by scanning electron microscopy (SEM) and transmission electron microscopy, confirmed selective deposition of Pt NPs on SnO2 nanoclusters formed on carbon surface. X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) analysis, cyclic voltammetry (CV) and CO stripping experiments revealed modification of the electronic properties of the Pt NPs photo-deposited on the oxide-carbon composite in comparison to Pt/C prepared by the carbonyl chemical route. Rietveld refinement was employed to identify existing phases of catalysts and to determine the crystallite size. Micro-strain and intrinsic stacking fault increased and decreased, respectively, as a function of crystallite size. Pt loadings were determined by inductively coupled plasma mass spectrometry (ICP-MS). The oxygen reduction reaction (ORR) activity of the electrocatalysts was investigated in acid media using the rotating disk electrode (RDE) system. Accelerated durability test (ADT) results showed that photo-deposited Pt nanoparticles onto SnO2 -C nanocomposite are more durable than those chemically deposited on carbon. Highlights: Pt/SnO2 -C composite electrocatalysts were prepared by photo-deposition. For comparison, platinum nanoparticles were chemically deposited on carbon. Metal-support interaction was studied by physical and electrochemical characterization. Pt/SnO2 -C catalysts showed high oxygen reduction activity in acid media. Durability of the Pt/SnO2 -C catalyst was superior in comparison with Pt/C.